2019
DOI: 10.1093/annonc/mdy509
|View full text |Cite
|
Sign up to set email alerts
|

Anti-EGFR-resistant clones decay exponentially after progression: implications for anti-EGFR re-challenge

Abstract: Background: Colorectal cancer (CRC) has been shown to acquire RAS and EGFR ectodomain mutations as mechanisms of resistance to epidermal growth factor receptor (EGFR) inhibition (anti-EGFR). After anti-EGFR withdrawal, RAS and EGFR mutant clones lack a growth advantage relative to other clones and decay; however, the kinetics of decay remain unclear. We sought to determine the kinetics of acquired RAS/EGFR mutations after discontinuation of anti-EGFR therapy.Patients and methods: We present the post-progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
167
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 187 publications
(183 citation statements)
references
References 30 publications
9
167
0
2
Order By: Relevance
“…Siena et al also found that the analysis of plasma samples showed that the first detected emergence of RAS mutations occurred a median of 3.6 months (range, 0.3-7.5 months) earlier than imaging progression. In addition, those who had emerging RAS mutations at progression had a similar median PFS to those patients who remained wildtype (29). These results suggested that except RAS mutations led to resistance to anti-EGFR antibodies, other mechanisms led to disease progression.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Siena et al also found that the analysis of plasma samples showed that the first detected emergence of RAS mutations occurred a median of 3.6 months (range, 0.3-7.5 months) earlier than imaging progression. In addition, those who had emerging RAS mutations at progression had a similar median PFS to those patients who remained wildtype (29). These results suggested that except RAS mutations led to resistance to anti-EGFR antibodies, other mechanisms led to disease progression.…”
Section: Discussionmentioning
confidence: 75%
“…Diaz et al (27) and Siravegna et al (28) found that in KRAS wild-type mCRC patients, KRAS mutation gradually increased during treatment with anti-EGFR antibody and gradually decreased after stopping treatment with anti-EGFR antibody or switching to other targeted drugs. The half-life of RAS mutations was 3.4 months (29). Siena et al also found that the analysis of plasma samples showed that the first detected emergence of RAS mutations occurred a median of 3.6 months (range, 0.3-7.5 months) earlier than imaging progression.…”
Section: Discussionmentioning
confidence: 97%
“…Serial liquid biopsies may have particular utility in which resistant mutations could be prospectively identified and treatment could be changed in real time. For example, liquid biopsies have been successfully applied to identify mechanisms of resistance for epidermal growth factor (EGFR) inhibitor in mCRC patients . Significant proportions of CRC harbor mutations in KRAS , BRAF , or NRAS that could cause resistance to an EGFR inhibitor, and these hotspot mutations are candidates for mutations detectable in plasma .…”
Section: Clinical Relevance Of Ctdna For Advanced Crcmentioning
confidence: 99%
“…For example, liquid biopsies have been successfully applied to identify mechanisms of resistance for epidermal growth factor (EGFR) inhibitor in mCRC patients. 63 Significant proportions of CRC harbor mutations in KRAS, BRAF, or NRAS that could cause resistance to an EGFR inhibitor, and these hotspot mutations are candidates for mutations detectable in plasma. 55,58 Previous reports showed that patients with RAS wild-type CRC in tissue, and plasma that is positive for KRAS and BRAF mutations can be resistant to the EGFR inhibitor.…”
Section: Treatment Response Clonal Evolution and Resistancementioning
confidence: 99%
See 1 more Smart Citation